Rancang Bangun Prototipe Sistem Pemantauan Tetes Cairan Infus Menggunakan Teknologi Internet Of Things (IoT) Dan Integrasi Perangkat Android - Syamsudin, Mariana; Rangga, Rangga; Satriyo, Satriyo (Electrical Network Systems and Sources, 2024)
This research focuses on developing an infusion fluid drip monitoring system prototype using Internet of Things (IoT) technology and Android device integration, which aims to increase efficiency and safety in managing intravenous fluids in medical units. So far, monitoring of infusion drops is still carried out manually by medical staff, In the meantime, the quality of infusion monitoring can affect the patient's condition and overall treatment results. the system consists of a liquid drop sensor connected to a microcontroller as a controller unit, with data sent via a wireless communication module to an IoT server. Users can access real-time information via an Android application that provides graphical displays of drip rate, infusion volume, and error warnings. Through simulation testing of clinical conditions, the results indicate that this system operates effectively and provide quick notification of significant changes in infusion fluids. This prototype can improve the efficiency of infusion fluid management, reduce the risk of dosing errors, and provide better monitoring of patient conditions in healthcare units. The possibility of integration with other technologies can also increase the functionality and security of these systems.Keywords: Infusion monitoring system, Internet of Things (IoT), Android, drip sensor, healthcare efficiency.